UiO-67 metal–organic gel material deposited on photonic crystal matrix for photoelectrocatalytic hydrogen production. Issue 25 (14th April 2020) - Sun, Shujian; Liao, Peisen; Zeng, Lihua; He, Lanqi; Zhang, Jianyong
Abstract : UiO-67 nanoparticles are precisely and uniformly anchored on a photonic crystal matrix via metal–organic gelation showing improved photoelectrocatalytic activity. Abstract : Robust UiO-67 metal–organic framework nanoparticles have been precisely and uniformly anchored on the surface of a photonic crystal via metal–organic gelation, resulting in a nanoscale UiO-67 composite. Mott–Schottky measurements indicate that UiO-67/B is an n-type semiconductor with electron conduction, and the band gap significantly decreases with the assistance of the photonic crystal matrix with a band gap of 0.75 eV. Benefiting from the abundant photoelectrons trapped from the photonic crystal, good hydrogen evolution reaction performance is achieved under light irradiation. The current density increases from 3.2 to 7.0 mA cm −2 at −0.6 V ( vs. RHE) for UiO-67/B. The optimized carrier density obtained from UiO-67/B is apparently increased 2.15 times under light irradiation for 30 min. This work provides a rational strategy to address the photo-capture and energy transfer issues of metal–organic frameworks under visible light irradiation for H2 production in artificial photosynthesis.